A new record of Tenodera fasciata (Olivier, 1792) (Insecta: Mantodea: Mantidae: Mantinae) for western India - Gopal Ambrushi Raut; Sunil Madhukar Gaikwad (Journal of Threatened Taxa, 2017)
Tenodera fasciata (Olivier, 1792) is reported for the first time from the Western Ghats.  The present record extends its known geographical range notably from the east towards western India for about 1,400km.  The finding of only two specimens in two years suggests its rarity.